2021
DOI: 10.3390/ijms221910424
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Type One Protein Phosphatase Participates in the Brassinosteroid Control of Root Growth via Activation of BES1

Abstract: Brassinosteroids (BRs) play key roles in diverse plant growth processes through a complex signaling pathway. Components orchestrating the BR signaling pathway include receptors such as kinases, transcription factors, protein kinases and phosphatases. The proper functioning of the receptor kinase BRI1 and the transcription factors BES1/BZR1 depends on their dephosphorylation by type 2A protein phosphatases (PP2A). In this work, we report that an additional phosphatase family, type one protein phosphatases (PP1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…Our results are consistent with the involvement of PP1R3 in stress responses, as Zhang et al (2020) reported a mutation in PP1R3 not only results in decreased seed germination and cotyledon greening but also retards seedling growth under ABA. Moreover, under exogenous brassinosteroid (BR), longer roots of TdPP1 overexpressing transgenic lines (Bradai et al, 2021) confirmed the participation of PP1 under hormonal stress in crops. Similarly, NaCl tolerance of OsPP1a overexpression genotypes (Liao et al, 2016) highlighted that PP1 could also rescue plants under abiotic stresses.…”
Section: Discussionmentioning
confidence: 77%
“…Our results are consistent with the involvement of PP1R3 in stress responses, as Zhang et al (2020) reported a mutation in PP1R3 not only results in decreased seed germination and cotyledon greening but also retards seedling growth under ABA. Moreover, under exogenous brassinosteroid (BR), longer roots of TdPP1 overexpressing transgenic lines (Bradai et al, 2021) confirmed the participation of PP1 under hormonal stress in crops. Similarly, NaCl tolerance of OsPP1a overexpression genotypes (Liao et al, 2016) highlighted that PP1 could also rescue plants under abiotic stresses.…”
Section: Discussionmentioning
confidence: 77%
“…Adjusting the root system architecture is one important clue for plants to conquer stress due to the root being the first defensive line to adapt to their environment [ 35 , 36 ]. Moreover, bes1-D had a shorter meristem size in the root [ 37 ]. BES1 regulates the vascular cell development in the root apex and root growth mediated by the type one protein phosphatases [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, bes1-D had a shorter meristem size in the root [ 37 ]. BES1 regulates the vascular cell development in the root apex and root growth mediated by the type one protein phosphatases [ 37 , 38 ]. Besides, BES1 acts to promote seedling growth in the auxin pathway [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, OsPP1a and TdPP1a play potential roles in the salt stress response in rice and wheat, respectively (Liao et al, 2016;Bradai et al, 2018). The latest study shows TdPP1 participates in the brassinosteroid control of root growth via activation of BRI1-EMS suppressor1 (BES1) (Bradai et al, 2021). In this research, we found that TOPP, as a novel regulator of the ATG1-ATG13 complex in Arabidopsis, promotes autophagy by dephosphorylating ATG13a and modulating the formation of the ATG1a-ATG13a complex under fixed-carbon (C) starvation.…”
Section: Introductionmentioning
confidence: 99%